MODEL OF TERRITORIAL INNOVATION IN LOCAL PRODUCTIVE ARRANGEMENT OF FAMILY AGRO-INDUSTRY - Liszbinski, Bianca Bigolin; Patias, Tiago Zardin; Sausen, Jorge Oneide; Ferreira, Gloria Charão; Brizolla, Maria Margarete Baccin (Mercator, 2021)
This study aims to analyze the movement characterized as Local Productive Arrangement (LPA) by Family Agro-industry and Diversity in the Médio Alto Uruguai and Rio da Várzea, located in the State of Rio Grande do Sul, in order to identify the type of territorial innovation model it represents. It is a case study and for its development, interviews were conducted with members of the governance of this productive arrangement, in addition to participant observation and documentary analysis. It was understood that the constitution of this APL took place as an alternative for economic and social development for rural families and their agro-industries, and its characteristics resemble it partly to industrial districts and partly to clusters. As for the similarity to industrial districts, specialization attributes were identified in a given sector, geographical approximation, understanding of innovation as a determinant of market differentiation, public support, competitive advantages and reduction of production costs. In terms of approaching the clusters, the decisive presence of the public entity for its implementation was identified, a competitive trend among agro-industries, demand for products, labor and infrastructure for production, in addition to the involvement of several entities, among them, universities. Keywords : Local Productive Arrangement, Family Agro-industry, Cluster, Industrial District.